Effectiveness of four vaccines in preventing SARS-CoV-2 infection in Almaty, Kazakhstan in 2021: retrospective population-based cohort study - Dilyara Nabirova; Dilyara Nabirova; Roberta Horth; Roberta Horth; Manar Smagul; Gaukhar Nukenova; Aizhan Yesmagambetova; Daniel Singer; Alden Henderson; Alexey Tsoy (Frontiers Media S.A., 2023)
BackgroundIn February 2021 Kazakhstan began offering COVID-19 vaccines to adults. Breakthrough SARS-CoV-2 infections raised concerns about real-world vaccine effectiveness. We aimed to evaluate effectiveness of four vaccines against SARS-CoV-2 infection.MethodsWe conducted a retrospective cohort analysis among adults in Almaty using aggregated vaccination data and individual-level breakthrough COVID-19 cases (≥14 days from 2nd dose) using national surveillance data. We ran time-adjusted Cox-proportional-hazards model with sensitivity analysis accounting for varying entry into vaccinated cohort to assess vaccine effectiveness for each vaccine (measured as 1-adjusted hazard ratios) using the unvaccinated population as reference (N = 565,390). We separately calculated daily cumulative hazards for COVID-19 breakthrough among vaccinated persons by age and vaccination month.ResultsFrom February 22 to September 1, 2021, in Almaty, 747,558 (57%) adults were fully vaccinated (received 2 doses), and 108,324 COVID-19 cases (11,472 breakthrough) were registered. Vaccine effectiveness against infection was 79% [sensitivity estimates (SE): 74%-82%] for QazVac, 77% (SE: 71%-81%) for Sputnik V, 71% (SE: 69%-72%) for Hayat-Vax, and 70% (SE: 65%-72%) for CoronaVac. Among vaccinated persons, the 90-day follow-up cumulative hazard for breakthrough infection was 2.2%. Cumulative hazard was 2.9% among people aged ≥60 years versus 1.9% among persons aged 18-39 years (p < 0.001), and 1.2% for people vaccinated in February-May versus 3.3% in June-August (p < 0.001).ConclusionOur analysis demonstrates high effectiveness of COVID-19 vaccines against infection in Almaty similar to other observational studies. Higher cumulative hazard of breakthrough among people ≥60 years of age and during variant surges warrants targeted booster vaccination campaigns.